The effects of music on cardiorespiratory endurance and muscular fitness in recreationally active individuals: a narrative review - Greco,Francesca; Grazioli,Elisa; Cosco,Loretta Francesca; Parisi,Attilio; Bertollo,Maurizio; Emerenziani,Gian Pietro (PeerJ, 2022)
Music is made up of several features (e.g., melody and rhythm) and it accompanies our life in different daily activities. During the last years, there was a growing interest in research about the music-related effects in the exercise domain. Music stimuli could act as an ergogenic effect leading to improvements in health-related and physical fitness components like cardiorespiratory endurance and muscular fitness. Moreover, listening to music may positively affect individuals’ psychological state which could lead to increased exercise adherence. Conflicting data exist regarding the effects of music on cardiorespiratory and muscle-strengthening exercises indicating that music’s characteristics (i.e., rhythm and musicality), studied samples (i.e., athletes and amateur) and methodology (i.e., self-selected music and research-selected music) might influence the results. Listening to music while exercising is becoming more frequent also in recreationally active individuals. While literature mainly focused on the effects of music in elite and amateur athletes, little data are available regarding recreationally active participants. Therefore, this review aims to summarize evidence regarding the effects of music on health-related physical fitness components in recreationally active individuals, specifically referring to cardiorespiratory endurance and muscular fitness. These outcomes will be helpful to all recreationally active participants to optimize the exercise protocol with the use of music.
Keywords: Aerobic exercise; Music; Strength training; Physical fitness